TRANSFORMATION OF HUMAN RESOURCE MANAGEMENT IN ISLAMIC EDUCATION INSTITUTIONS: CASE STUDY OF PONDOK PESANTREN ANNIDA - M. Gerry Naufal R. G.; Achmad Ghazali (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Human Capital Management (HCM) is critical to guaranteeing the sustainability and competitiveness of educational institutions, notably Islamic boarding schools (pesantren).  This research will examine the implementation of HCM at Annida Islamic Boarding School Cirebon, identify difficulties, and provide strategic solutions to improve human resource management.  Using a qualitative method, primary data were gathered through surveys and interviews with educators and management, while secondary data were gained from institutional records and academic literature. The findings show that Annida Islamic Boarding School confronts major issues in numerous important areas of human capital management, such as leadership practices, employee engagement, performance assessment, and career development. Low motivation and uneven instruction are exacerbated by the lack of a systematic performance assessment system and professional development opportunities. The lack of a structured performance appraisal system and lack of professional development opportunities contribute to low motivation and inconsistent education quality. In addition, the decision-making process is highly centralized, limiting employee autonomy and innovation. To address these topics, this study proposes a strategic framework based on Bassi and McMurrer's HCM-Rife model, highlighting structured performance appraisals, development programs for managers, and a transparent career progression system. By integrating modern principles of human resource management, Anida Islamic boarding school can improve the quality of education, increase employee loyalty, and enhance competitiveness in the field of Islamic education.